2020
DOI: 10.1055/a-1090-0788
|View full text |Cite
|
Sign up to set email alerts
|

Anterior versus posterior approach in peroral endoscopic myotomy (POEM): a systematic review and meta-analysis

Abstract: Background Peroral endoscopic myotomy (POEM) is increasingly being used as the endoscopic treatment option for achalasia. Data are limited as to the comparative efficacy of anterior vs. posterior myotomy. Methods We searched multiple databases from inception to August 2019 to identify studies reporting on POEM. We selected studies that reported on the outcomes of POEM, along with information on myotomy approach. We performed a comparative analysis of clinical success, gastroesophageal reflux disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 18 publications
2
36
1
3
Order By: Relevance
“…Off PPI, n/N (%) ageal acid exposure in the posterior myotomy group. Two meta-analyses [5,6] have established the comparable shortterm clinical efficacy and safety of both approaches. The current study contributes comparative data between both approaches during medium-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Off PPI, n/N (%) ageal acid exposure in the posterior myotomy group. Two meta-analyses [5,6] have established the comparable shortterm clinical efficacy and safety of both approaches. The current study contributes comparative data between both approaches during medium-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In current clinical practice, myotomy orientation is largely driven by operator preference. In recent years, several studies have focused on comparing the two approaches, revealing similar efficacy [5,6] and possibly lower risk of post-POEM gastroesophageal reflux with the posterior approach [6]. However, the limitation remains the lack of longitudinal data, as all comparative studies reported outcomes with a follow-up of less than 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the only options available for treatment of achalasia were pharmacological treatments, Botox, pneumatic dilation, and surgery 29 . However, technological progress and the development of minimally invasive surgery have allowed the creation of NOTES 16 17 associated with submucosal dissection 18 , and the called POEM, revolutionizing the treatment of achalasia 30 31 32 33 .…”
Section: Discussionmentioning
confidence: 99%
“…All the approaches have similar efficacy with no clinically relevant difference in adverse events or incidence of GERD. [48][49][50][51][52] Muscle fibres are cut in 1-2 o'clock and 5-6 o'clock position in anterior and posterior myotomy, respectively (Fig. 3).…”
Section: Technique Of Poem and Variationsmentioning
confidence: 99%